Students' approaches to learning (SALs): Validation and psychometric properties of a tool measurement - Omar Jiyed; Anouar Alami; Lhoussaine Maskour; Bouchta El Batri; Nadia Benjelloun; Moncef Zaki (Wolters Kluwer Medknow Publications, 2023)
BACKGROUND: Deep learning is an important outcome of the higher education and is mostly determined by students' approaches to learning (SALs). The latest version of the Study Process Questionnaire (SPQ) is one of the most used instruments assessing SALs. Many studies from various contexts have either validated or used this famous tool. But none of them-to the best of our knowledge-stem from the Moroccan tertiary context. The current study fills this gap by first: Getting a local translation of the questionnaire following the standardized methodological process and secondly to update the validity and psychometric properties of the construct. MATERIALS AND METHODS: Arabic back translation was performed. Data were collected among tertiary scientific students. Descriptive statistics, Cronbach's coefficient alpha, and confirmatory factor analysis were carried out under SPSS version 22. RESULTS: A strong fit of the dichotomic construct (deep and surface) was found, whereas the hierarchical models were disappointing. CONCLUSIONS: Following the standards of the psychometrics' validation, this Arabic version could be used only in first-order factor model to evaluate the deep and surface approach within tertiary education in Moroccan context.